Bineolingual upbringing or bilingual upbringing in non-native families: linguistic habits and strategies - Lozano-Martínez, Laura (Complutense Journal of English Studies, 2026)
The knowledge of additional languages is a desirable value nowadays. Raising a bilingual child yields numerous advantages (Baker, 2014; Bialystok, 2001; Romaine, 1995). In order to help their children acquire and learn a foreign language (FL), mainly English, most parents decide to raise their children in a FL that is also foreign to them and that is not the language of the community. However, strategies and linguistic practices in BiNeoLingual (BNL) Upbringing (or bilingual upbringing by non-native parents) have not yet been studied using a statistically significant sample size to draw generalizable conclusions. There is a need to adequately portray and analyse this emerging sociolinguistic phenomenon (Lozano-Martínez 2019). In this quantitative study, through a simple random sampling, 571 families out of the 2010 that participated in a questionnaire were identified as using English as a FL with their children. Nevertheless, “family linguistic planning is crucial to children’s linguistic development” (Lozano-Martínez 2019, 235). Dealing with strategies, One Parent-One Language (OPOL) is the most well-known but, according to the results, OPOL is not the most followed strategy by BNL families. Statistical tests also show that strategies depend on different factors and are often mixed in the BNL family.